The effectiveness of prophylactic antibiotic prescribing (preventive) before cesarean section and prescribing after umbilical cord clamping in the infection after cesarean section: a triple-blind randomized clinical trial - Zeinab Shahbazzadeh; Mozhdeh Navinezhad; Masoumeh Sharifzadeh; Parastoo Amiri; Mitra Eftekhar Yazdi (Mashhad University of Medical Sciences, 2021)
Introduction: Cesarean section is one of the most common surgeries in midwifery. Due to the lack of a coordinated approach for antibiotic injection before cesarean section and not knowing the advantages and disadvantages of antibiotic injection time on mother and fetus, therefore, this study was performed with aim to compare the effectiveness of prophylactic antibiotics prescribing before cesarean section with prescribing after umbilical cord clamping to prevent infection after cesarean section. Methods: This triple-blind randomized clinical trial study was performed on 150 women with cesarean delivery in Shahidan Mobini Hospital of Sabzevar in 2019. In the intervention group, antibiotic was administered after umbilical cord clamping and in the control group, antibiotic was administered before cesarean section incision. Symptoms of infection were assessed using the checklist on the 3rd, 10th, and 14th days. Data were analyzed by SPSS software (version 19) and Chi-square, Exact Fisher and Mann-Whitney tests. p < 0.05 was considered statistically significant. Results: On the 3rd day after surgery, none of the patients in the two groups had infection. On the 10th day, 1 patient (1.3%) in the intervention group and 3 (4%) in the control group developed symptoms of infection (p = 0.31). On the 14th day after surgery, 1 patient (1.3%) in the control group and 5 (6.7%) in the intervention group had symptoms of infection (p = 0.10). The difference of infection on the 10th and 14th days was not statistically significant in the two groups. Conclusion: Antibiotic injection after umbilical cord clamping and one hour before surgery does not differ in the rate of postoperative infection.